Mechanisms of Platelet Dysfunction and Response to DDAVP in Patients with Congenital Platelet Function Defects - Rao, A Koneti; Ghosh, Sikha; Sun, Ling; Yang, Xu; Disa, Jyoti; Pickens, Peter; Polansky, Marcia (Thrombosis and Haemostasis, 1995)
To examine the impact of the underlying defective platelet mechanism on the response to 1-desamino-8-D-arginine vasopressin (DDAVP, Desmopressin), we studied the effect of intravenous infusion of 0.3 μg/kg of DDAVP in a randomized double blind placebo-controlled trial with cross-over in 18 carefully characterized patients with congenital platelet defects (CPD) and BT ≥9 min. Eleven patients had normal dense granule stores and normal thromboxane A2 (TxA2) production (Group I), 3 patients had normal granule stores but impaired TxA2 production (Group II), and 4 had δ-storage pool deficiency (Group III). DDAVP shortened BT at 50 min (DDAVP 14.6 ± 2.2 vs placebo 19.6 ± 2.3 min; n = 18; mean ± SE; p = 0.003) and 4h (17.0 ± 2.2 vs 19.6 ±2.1 min, p = 0.055), and raised plasma FVIIIC and von Willebrand factor (vWF). At 50 min DDAVP shortened BT by ≥5 min in 8 of 11 Group I patients (mean 9.7 ± 1.3 vs 16.3 ± 2.8 min; p <0.008), 1 of 3 Group II patients (11.9 ± 3.9 vs 17.7 ± 6.6; p = NS) and none of Group III patients (mean 30 min both arms). Ten patients (Group I or II) were managed successfully during surgical procedures with DDAVP alone. We conclude that DDAVP shortens BT in majority of CPD patients with normal dense granule stores and suggest that BT response may be dependent on the underlying platelet defect. DDAVP is a useful modality in management of selected patients, particularly those with normal dense granule stores.